Persepsi Manajer Perawat tentang Keselamatan Pasien - Wiranata, I Nyoman; Swarjana, I Ketut; Negara, I Gusti Ngurah Made Kusuma; Nuartini, Ni Nyoman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to review the scope of the role of nurse managers in managing patient safety in hospitals. The method used was a literature review. There were 12 articles analyzed obtained from online databases on Pubmed, Science Direct, and other sources. The results of this study indicate that nurse managers have a high perception and positive attitude toward patient safety culture, and the leadership climate in the hospital creates a patient safety culture. In conclusion, nurse managers have a high perception of patient safety, and nurse managers' leadership styles and strategies play a role in increasing nursing staff's perception of patient safety and patient safety culture. Keywords: Patient Safety, Nurse Manager, Hospital